2018
DOI: 10.1364/optica.5.001338
|View full text |Cite
|
Sign up to set email alerts
|

Free space laser telecommunication through fog

Abstract: Atmospheric clearness is a key issue for free space optical communications (FSO). We present the first active method to achieve FSO through clouds and fog, using ultrashort high intensity laser filaments. The laser filaments opto-mechanically expel the droplets out of the beam and create a cleared channel for transmitting high bit rate telecom data at 1.55 µm. The low energy required for the process allows considering applications to Earth-satellite FSO and secure ground based optical communication, with class… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 40 publications
1
47
0
1
Order By: Relevance
“…When only one pulse of the train is used (bearing 0.48 mJ as in the pulse train), no transmission gain is observed, which suggests that the plasma generation of individual pulses of the train is negligible. Conversely if the whole energy of the pulse train, 3.8 mJ, is concentrated in a single pulse, plasma generation and filamentation are initiated, and we observe the associated acoustic wave clearing process seen previously [8,9], i.e. −8 dB, which exceeds the quantum wake clearing process with 8 pulses.…”
Section: Methodsmentioning
confidence: 43%
See 2 more Smart Citations
“…When only one pulse of the train is used (bearing 0.48 mJ as in the pulse train), no transmission gain is observed, which suggests that the plasma generation of individual pulses of the train is negligible. Conversely if the whole energy of the pulse train, 3.8 mJ, is concentrated in a single pulse, plasma generation and filamentation are initiated, and we observe the associated acoustic wave clearing process seen previously [8,9], i.e. −8 dB, which exceeds the quantum wake clearing process with 8 pulses.…”
Section: Methodsmentioning
confidence: 43%
“…Until recently no active method for opening clear optical transmission channels through clouds or fog was available. The propagation of ultrashort and high intensity lasers through the atmosphere provided a radically new concept, based on plasma generation inherent to laser filamentation [7][8][9]. Laser filaments are self-sustained light structures with a typical core diameter d core ∼ 100 µm (at 800 nm) and up to hundreds of meters in length, orders of magnitude beyond the linear diffraction limit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise timescales of these different processes depend on the experimental conditions. Investigations of photoionization have led to a better understanding of plasmas [1,2] and filamentation [3,4], as well as the development of plasma and air waveguides [4][5][6][7] that might be exploited for laser-based free space communication in the presence of fog [8]. A good understanding of plasma dynamics is also crucial in experiments at MHz pulse repetition rates in the strong field regime, for example in high harmonic generation within femtosecond enhancement cavities [9] and the generation of broadband deep and vacuum ultraviolet via dispersive wave emission in gas-filled hollow-core photonic crystal fibers (HC-PCFs) [10].…”
Section: Introductionmentioning
confidence: 99%
“…The long-distance transmission of the filament offers many potential applications. Wolf et al [179] reported a free space laser telecommunication through the fog. They use a filament-induced shock wave to radially expel the droplets out of the beam from the air it sweeps, then providing a clean channel for telecom laser transmission, which has the potential to be applied to Earth-satellite free-space optical communications and secure ground-based optical communications.…”
Section: Femtosecond Lasers Guided High Voltage Electric Dischargesmentioning
confidence: 99%